Carly L. Crouch & Jonathan Stökl (eds.): In the Name of God. The Bible in the Colonial Discourse of Empire - Becker, Judith (Entangled Religions, 2015)
This contribution offers a review ofCarly L. Crouch & Jonathan Stökl (eds.): In the Name of God. The Bible in the Colonial Discourse of Empire, Biblical Interpretation Series 126.Leiden: Brill, 2014. viii and 192 pages, € 98, ISBN 978-900-425-8334.